IDEOLOGY IN EDUCATION NEWS IN KOMPAS, MEDIA INDONESIA, AND REPUBLIKA NEWSPAPERS (Critical Discourse Analysis) - ROSITA ANGGRAINI (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2016)
This study aims to gain deep understanding of ideology in education news in Kompas, Media Indonesia, and Republika newspapers. The method used in this research is qualitative research with content analysis base on the critical discourse analysis theoryby Norman Fairclough that combines three dimensions in communication (text, discourse practice and socio-cultural practice). The data in this research are educational news that is published in Kompas,Media Indonesia, and Republika newspapers in the year 2014. The finding shows that the diversity of ideologies in the text indicate the differences of ideologies of the three newspapers. Ideologies in the discourse practice describe the factors that influence the production of text that are accomodate the issue, routine media and immediacy,selecting and sorting, and influence the view of readers; and affect the consumption of text, i.e read widespread information,integrateprint and digital media, follow the media agenda, read media content as needed, and highly need mass media information.Ideologies in socio-cultural practice describe educational policies in Indonesia.